2018
DOI: 10.31674/mjmr.2018.v02i02.006
|View full text |Cite
|
Sign up to set email alerts
|

Moringa Oleifera Leaf Extract Loaded Hydrogel for Diabetic Wound Healing

Abstract: Diabetic wounds (DW) are a chronic, non-healing wound on the feet of diabetic patients that pose a serious challenge to world health. Around 84% of diabetic patients undergo lower leg amputations. Though numerous topical and systemic drugs have been used to heal the DW, these drugs have led to the emergence and subsequent rapid overgrowth of resistant bacterial strains, side effects and toxicity. Many herbal plants have very important role in wound healing because they promote the natural repair mechanisms. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Our search from the six databases produced a total of 80 related articles. After removing duplicates, 59 articles were screened and 18 articles were included [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], as summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our search from the six databases produced a total of 80 related articles. After removing duplicates, 59 articles were screened and 18 articles were included [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], as summarized in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the studies indicate that M. oleifera was applied topically and formulated as gel (six studies [ 30 , 39 , 44 , 47 ] followed by using the extract in the form of paste, patch, or film dressing (five studies [ 30 , 33 , 36 , 40 ] and the remaining an ointment (three studies [ 34 , 41 , 42 ]. Two studies reported oral administration of M. oleifera aqueous extracts (two studies [ 38 , 43 ] while another two reported dual administration of both topical (ointment and aqueous extract) and oral (aqueous extracts) (two studies [ 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted on a hyperglycemic animal model utilizing the leaves of M. oleifera (Moringaceae family) showed specific characteristics such as modulation of inflammatory mediators, improved wound contraction, and epithelialization [36]. Table 2 contains detailed properties of M. oleifera in treating diabetic foot ulcers.…”
Section: Moringa Oleifera Lammentioning
confidence: 99%